2019
DOI: 10.21608/ajnsa.2019.6159.1134
|View full text |Cite
|
Sign up to set email alerts
|

First Trial to Assess Gamma-Irradiation and Diatomaceous Earth Combination on Mortality of some Stored Product Insects

Abstract: This study was designed to characterize the combination of gamma-irradiation and food grade diatomaceous earth(Wolf Creek ranch, California, USA) as diatomaceous earth formulation (DE) treatment against three of stored product insect pests [Sitophilusgranarius(L), Triboliumcastaneum(Herbst.) and Rhyzoperthadominica,(F)]in the laboratory. The study was assessed the killing effect of γ-irradiation at 0,50,100 and 250 Gray against these pests. As well as 0, 0.5, 1.0 and 1.5 g/kg (w/w) concentrations of DE formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chiluwal et al (2019) exposed C. chinensis adults to gamma radiation (0, 200, 300, 400, 500, and 600 Gy) and found that female fecundity, hatchability, and adult fertility reduced after the dose of 300 Gy. Sileem et al (2019) studied the effect of gamma-irradiation in combination with food-grade diatomaceous earth (DE) against S. granarius, T. castaneum, and R. dominica. Among their treatments, the combination of 100 Gy gamma-radiation exposure with DE @ 1 g/kg was found significant with complete mortality.…”
Section: Irradiation (Ionizing Radiations)mentioning
confidence: 99%
“…Chiluwal et al (2019) exposed C. chinensis adults to gamma radiation (0, 200, 300, 400, 500, and 600 Gy) and found that female fecundity, hatchability, and adult fertility reduced after the dose of 300 Gy. Sileem et al (2019) studied the effect of gamma-irradiation in combination with food-grade diatomaceous earth (DE) against S. granarius, T. castaneum, and R. dominica. Among their treatments, the combination of 100 Gy gamma-radiation exposure with DE @ 1 g/kg was found significant with complete mortality.…”
Section: Irradiation (Ionizing Radiations)mentioning
confidence: 99%
“…The control of storage pests was depending on the use of chemical techniques; these compounds have been recorded to be operative towards C. maculatus and other insects [3]. Because of the problems of numerous insecticides including; unavailability, high persistence, being expensive, resistance and risks to the environment and public health, research is being oriented to alternative control measures such as heat treatments, use of insect hormones, bio-pesticides, irradiation, and integrated pest management [15,31]. Irradiation was used as phytosanitary management for agricultural products since the International plant protection convention (IPPC) mentioned the recommendations and simplified trade based on these phytosanitary methods [15,16].…”
Section: Introductionmentioning
confidence: 99%